Answer:
b -3,3 c 6,9 hope this helps
(6 + 5x)(7x + 3) = 42x + 18 + 35x^2 + 15x = 35x^2 + 57x + 18
Answer:
Step-by-step explanation:
Answer:
yes,yes,yes,no :) hope it helps
Step-by-step explanation:
Elimination Method
![\begin{gathered} -2X+Y-2Z=-8 \\ 7X+Y+Z=-1 \\ 5X+2Y-Z=-9 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20-2X%2BY-2Z%3D-8%20%5C%5C%207X%2BY%2BZ%3D-1%20%5C%5C%205X%2B2Y-Z%3D-9%20%5Cend%7Bgathered%7D)
If we multiply the equation 3 by (-1) we obtain this:
![\begin{gathered} -2X+Y-2Z=-8 \\ 7X+Y+Z=-1 \\ -5X-2Y+Z=9 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20-2X%2BY-2Z%3D-8%20%5C%5C%207X%2BY%2BZ%3D-1%20%5C%5C%20-5X-2Y%2BZ%3D9%20%5Cend%7Bgathered%7D)
If we add them we obtain 0, therefore there are infinite solutions. So, let's write it in terms of Z
1. Using the 3rd equation we can obtain X(Y,Z)
![\begin{gathered} 5X=-9-2Y+Z \\ X=\frac{-9-2Y+Z}{5} \\ \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%205X%3D-9-2Y%2BZ%20%5C%5C%20X%3D%5Cfrac%7B-9-2Y%2BZ%7D%7B5%7D%20%5C%5C%20%20%5Cend%7Bgathered%7D)
2. We can replace this value of X in the 1st and 2nd equations
![\begin{gathered} -2\cdot(\frac{-9-2Y+Z}{5})+Y-2Z=-8 \\ 7\cdot(\frac{-9-2Y+Z}{5})+Y+Z=-1 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20-2%5Ccdot%28%5Cfrac%7B-9-2Y%2BZ%7D%7B5%7D%29%2BY-2Z%3D-8%20%5C%5C%207%5Ccdot%28%5Cfrac%7B-9-2Y%2BZ%7D%7B5%7D%29%2BY%2BZ%3D-1%20%5Cend%7Bgathered%7D)
3. If we simplify:
![\begin{gathered} \frac{-9Y+12Z-63}{5}=-1 \\ \frac{9Y-12Z+18}{5}=-8 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20%5Cfrac%7B-9Y%2B12Z-63%7D%7B5%7D%3D-1%20%5C%5C%20%5Cfrac%7B9Y-12Z%2B18%7D%7B5%7D%3D-8%20%5Cend%7Bgathered%7D)
4. We can obtain Y from this two equations:
![\begin{gathered} Y=-\frac{-12Z+58}{9} \\ \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20Y%3D-%5Cfrac%7B-12Z%2B58%7D%7B9%7D%20%5C%5C%20%20%5Cend%7Bgathered%7D)
5. Now, we need to obtain X(Z). We can replace Y in X(Y,Z)
![\begin{gathered} X=\frac{-9-2Y+Z}{5} \\ X=\frac{-9-2(-\frac{-12Z+58}{9})+Z}{5} \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20X%3D%5Cfrac%7B-9-2Y%2BZ%7D%7B5%7D%20%5C%5C%20X%3D%5Cfrac%7B-9-2%28-%5Cfrac%7B-12Z%2B58%7D%7B9%7D%29%2BZ%7D%7B5%7D%20%5Cend%7Bgathered%7D)
6. If we simplify, we obtain:
![X=\frac{-3Z+7}{9}](https://tex.z-dn.net/?f=X%3D%5Cfrac%7B-3Z%2B7%7D%7B9%7D)
7. In conclusion, we obtain that
(X,Y,Z) =